Purposeful Entanglements: A New Materialist Analysis of Transformative Interviews - Marn, Travis M.; Wolgemuth, Jennifer R. (Qualitative Inquiry, 2017)
In this article, we explore transformative interviewing through the lens of new materialism. Rather than viewing transformation through a humanist perspective that centralizes a transcendent self, we draw upon Barad’s agential realism to reconsider transformation following the ontological turn. Thinking with agential realism, we engaged two interview studies, one on biracialism and one on masculinity, to demonstrate how the materiality of our interviews (e.g., research bodies, computer programs, questionnaires) intra-acted with our participants to both facilitate and hinder our attempts at transformation. We conclude by theorizing transformation as a type of purposeful entanglement that proceeds from the material-discursive intra-actions of our inquiries.
Keywords: dept.cur

Joyfully engaged in multimodal learning - Shaw, Louise J. (Promoting social emotional learning in the classroom: Creativity, connections, and engagement, 2017)
Keywords: dept.cur

It’s all Greek: Ancient history as a community journey - Shaw, Louise J. (Impacting literacy through home and community connections, 2017)
Keywords: dept.cur

Teaching students to write: Arguing against the overuse of argument - Randall, Régine; Mercurio, Mia Lynn (Kappa Delta Pi Record, 2017)
This personal editorial written by two education professors considers the Common Core State Standards and argues against the overuse of argument in the teaching of writing. © Kappa Delta Pi.
0 citations (Crossref) [2023-10-31]
Keywords: Common core; Writing; dept.cur; dept.sed

Exploring English and Spanish rhyme awareness and beginning sound segmentation skills in prekindergarten Spanish-speaking English Learners - Raynolds, Laura B.; López-Velásquez, Angela; Olivo Valentín, Laura E. (Reading and Writing, 2017)
Twenty-five 4- and 5-year-old Spanish-speaking English Learners (ELs) were tested in order to compare their English and Spanish performance in two phonological awareness skills: Rhyme awareness (RA) and beginning sound segmentation (BSS). The children had received formal instruction of phonological awareness, with an emphasis on RA and BSS for 1 year and in English only, using the Opening the World of Learning curriculum (Schickedanz & Dickinson, 2005). The results showed that the children scored higher on the English BSS than on the English RA tests (p ¡ .001), even though RA is generally considered to be an earlier developing skill than BSS among English-monolingual children. No significant difference was found between the English BSS and Spanish BSS tests despite the fact that the children had received English-only instruction in these phonological awareness skills for 1 year. The results are discussed in terms of the possible impact of the similarities and differences between the Spanish and English linguistic structures on the learning and cross-linguistic transfer of phonological awareness skills in young Spanish-speaking ELs.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000398445600003, lens.org/009-289-778-807-372 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Beginning sound segmentation; English-only instruction; Phonological awareness; Prekindergarten; Rhyme awareness; Spanish-speaking English Learners; dept.cur; dept.sed; peer-reviewed